Tailoring communications to the evolving needs of patients throughout the cancer care trajectory: a qualitative exploration with breast cancer patients. Issue 1 (December 2016) - Shim, Eun-Jung; Park, Jee Eun; Yi, Myungsun; Jung, Dooyoung; Lee, Kwang-Min; Hahm, Bong-Jin
Abstract Background Doctor-patient communication is a crucial aspect of patient care. This study explored the communication experience of patients in a cancer consultation over the course of the cancer continuum. Methods In-depth interviews with seven breast cancer patients were carried out. Results Themes related to communication experiences across the five phases of cancer consultation, from diagnosis to recurrence, were identified. The most salient issue is that patients also perceived cancer as 'a disease of the mind', which is not adequately cared for in consultation. This highlights the notion that cancer care providers should provide appropriate care for the psychological dimensions of the cancer experience with an empathic and sincere attitude during consultations. To this end, non-verbal aspects of communication that convey caring, support, and respect seem important. Furthermore, patients perceived that the consultation time was far shorter then they needed and reported that they felt pressured for time. Moreover, the stance taken by patients and the needs and preferences of patients varied across the phases of the cancer trajectory. As patients progressed through the phases of their treatment, they assumed more active roles in the course of their care and the need for more detailed information and questioning increased. Thus, ensuring that patients have opportunities to ask questions in the consultation is important. Conclusion Current findings suggest that the efficacy of communication varies depending on which phase patients are in and that effective communication should be tailored to these evolving needs and preferences of breast cancer patients. Also, patients perceived that the consultation did not adequately address their need for information related to their care or their emotional issues associated with the cancer experience. It is therefore important to address their needs by paying particular attention to non-verbal aspects of communication that convey empathy and respect toward patients, as well as allowing patients to ask questions.